2021
DOI: 10.1111/jgs.17105
|View full text |Cite
|
Sign up to set email alerts
|

Worries, attitudes, and mental health of older adults during the COVID‐19 pandemic: Canadian and U.S. perspectives

Abstract: Background/Objectives: Differences in older adults' worry, attitudes, and mental health between high-income countries with diverging pandemic responses are largely unknown. We compared COVID-19 worry, attitudes towards governmental responses, and self-reported mental health symptoms among adults aged ≥55 in the United States and Canada early in the COVID-19 pandemic. Design: Online cross-sectional survey administered between April 2nd and May 31st in the United States and between May 1st and June 30th, 2020 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
0
14
0
3
Order By: Relevance
“…Although the current research was a part of a broader Slovak study involving a general adult sample as well as an older adult sample (Bavo ˇlár et al, 2021), the results presented in this paper cannot be fully compared with the general adult sample as some variables were measured with different instruments. However, the current findings can be compared with similar research studies conducted on a cohort of older adults in different countries during the COVID-19 pandemic (Ahorsu et al, 2020;Bergman et al, 2020;Bidzan-Bluma et al, 2020;Carriedo et al, 2020;García-Portilla et al, 2020;Grossman et al, 2021;Han et al, 2021;Jordan et al, 2021;Parlapani et al, 2020;Reppas-Rindlisbacher et al, 2021;Robb et al, 2020;Shrira et al, 2020;Tyler et al, 2021;Zhou et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…Although the current research was a part of a broader Slovak study involving a general adult sample as well as an older adult sample (Bavo ˇlár et al, 2021), the results presented in this paper cannot be fully compared with the general adult sample as some variables were measured with different instruments. However, the current findings can be compared with similar research studies conducted on a cohort of older adults in different countries during the COVID-19 pandemic (Ahorsu et al, 2020;Bergman et al, 2020;Bidzan-Bluma et al, 2020;Carriedo et al, 2020;García-Portilla et al, 2020;Grossman et al, 2021;Han et al, 2021;Jordan et al, 2021;Parlapani et al, 2020;Reppas-Rindlisbacher et al, 2021;Robb et al, 2020;Shrira et al, 2020;Tyler et al, 2021;Zhou et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…Um estudo comparativo entre Estados Unidos da América e Canadá, durante os primeiros meses da pandemia da COVID-19, concluiu que idosos dos Estados Unidos se sentiram menos apoiados pelo governo federal e apresentaram sintomas de depressão e ansiedade elevados em comparação aos idosos do Canadá (Reppas-Rindlisbacher et al, 2021). Na Áustria, a solidão foi maior durante o confinamento em comparação com a fase subsequente de reabertura, ou seja, medidas rápidas de combate ao vírus, realizadas pelo governo federal, evitam que a longo prazo haja efeitos permanentes, principalmente em idosos (Stolz, et al, 2021).…”
Section: Discussionunclassified
“…These findings are consistent with those in other countries that have documented the importance of trust in science and government officials. For example, one study found that older adults in the U.S. felt less supported by their federal government compared to older Canadians at the beginning of the pandemic ( Reppas-Rindlisbacher et al, 2021 ). Additionally, a U.K. study found that opinions related to the COVID-19 pandemic were largely dependent on trust in science and health officials, though underlying societal divides such as income and educational disparities explain some of these differences ( Maher et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%